Case Report: 3D-CISS and PC-MRI in the diagnosis and surgical planning of hydrocephalus secondary to presumptive lateral aperture obstruction in a dog - Tauro, Anna; Kurihara, Manabu; Macri, John; Early, Peter; Mariani, Christopher L.; Olby, Natasha J.; Muñana, Karen R.; Lewis, Melissa J.; Sjalander-Dillenbeck, Linda (Frontiers in Veterinary Science, 2025)
IntroductionThis report describes the use of three-dimensional constructive interference in steady state (3D-CISS) and phase-contrast magnetic resonance imaging (PC-MRI) sequences to investigate the etiology of severe hydrocephalus, and the subsequent surgical management and long-term outcome.Case presentationA 5-month-old male Rhodesian Ridgeback presented with acute, progressive neurological signs culminating in non-ambulatory tetraparesis. Clinical and imaging findings were consistent with non-communicating tetraventricular hydrocephalus with concurrent severe syringomyelia, but conventional MRI failed to identify the cause of cerebrospinal fluid (CSF) flow obstruction. Following failure of medical management, advanced MRI sequences were performed to clarify the underlying etiology and guide surgical planning. These included 3D-CISS for high-resolution anatomical assessment and PC-MRI for dynamic evaluation of CSF flow. The findings demonstrated patent intraventricular CSF flow and no evidence of arachnoid septations within the fourth ventricle, thereby excluding a fourth ventricle arachnoid diverticulum. Instead, the imaging findings supported a presumptive diagnosis of hydrocephalus secondary to lateral aperture occlusion. A ventriculoperitoneal (VP) shunt was placed, resulting in substantial clinical improvement, although mild residual cerebellar deficits persisted. Five months later, the dog experienced acute deterioration. Computed tomography revealed fracture of the distal catheter at the level of its abdominal wall anchoring site, likely due to progressive tension as the dog grew, resulting in the catheter snapping into two segments. Revision surgery restored CSF diversion and led to rapid clinical recovery. The patient remains neurologically stable at 28 months of age, 15 months post-revision.ConclusionAdvanced MRI sequences, particularly 3D-CISS and PC-MRI, were instrumental in supporting the presumptive diagnosis of lateral aperture obstruction as the underlying cause of hydrocephalus and in guiding an individualized, effective surgical strategy. This case highlights the diagnostic and clinical value of advanced MRI techniques in managing complex hydrocephalus.